A lipid nanoparticle encapsulated CPA-CTD mRNA vaccine provides protection against Clostridium perfringens-driven diseases - Jia, Qi; Xiang, Haoyu; Le, Ting; Wang, Jing; Chang, Jitao; Wang, Fang; Sun, Chao; Tai, Wanbo; Jiang, Zhigang; Yin, Xin (Frontiers in Immunology, 2026)
IntroductionClostridium perfringens (C. perfringens), a ubiquitous Gram-positive bacterium in the environment and mammalian gut flora, is a leading cause of enterotoxemia in animals, necrotizing enteritis in humans and animals, and gas gangrene in both, attributed to its diverse exotoxin profile. Alpha-toxin, a pivotal virulence factor produced by all C. perfringens serotypes, plays a central role in the pathogenicity of these diseases.MethodsHere, we engineered a lipid nanoparticle encapsulated CPA-CTD mRNA vaccine targeting the conserved C-terminal domain of C. perfringens alpha-toxin and rigorously assessed its immunogenicity and protective efficacy in mouse and bovine models.ResultsThe CPA-CTD mRNA vaccine induced strong humoral and cellular immune responses in mice, particularly in promoting the rapid production of specific IgG and mucosal IgA antibodies, as well as enhancing T cell immune responses, surpassing conventional subunit vaccines. Protection was confirmed in dual challenge models --enterotoxemia and gas gangrene --where the vaccine provided complete immunity against lethal doses of alpha-toxin and C. perfringens infection. In cattle, the CPA-CTD mRNA vaccine induced high-titer IgG antibodies and toxin-neutralizing antibodies. Notably, immunization of pregnant cows led to efficient transfer of these antibodies via colostrum to newborn calves, providing passive protection.DiscussionThese results demonstrate that the CPA-CTD mRNA vaccine provides rapid and robust immune protection against C. perfringens alpha-toxin-associated diseases, with promising potential for applications in both veterinary and human health.